2022
DOI: 10.1002/ca.23932
|View full text |Cite
|
Sign up to set email alerts
|

Lateral branches of the facial artery and its clinical implications

Abstract: The facial artery is the main artery supplying blood to the face and is known to have facial branches of the inferior labial, superior labial, lateral nasal and angular arteries.These known major branches of facial artery run medially, however, there are sometimes branches of the facial artery heading laterally. The purpose of the present study was to investigate the lateral branches of the facial artery in face. We dissected facial branches of the facial artery in 74 cadaveric hemifaces. We investigated the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…On the other hand, in the study of Padur et al [32], the FA gave off lateral branches posteriorly. These pre-masseteric branches were considered FA variations [30,33]. One of the variations other than pre-masseteric branches was the hypoplastic/rudimentary type [3,6,7,10,25,28].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, in the study of Padur et al [32], the FA gave off lateral branches posteriorly. These pre-masseteric branches were considered FA variations [30,33]. One of the variations other than pre-masseteric branches was the hypoplastic/rudimentary type [3,6,7,10,25,28].…”
Section: Discussionmentioning
confidence: 99%
“…Niemann et al [28] reported a linguofacial trunk (12.82%) and a high origin of FA (2.56%), and males revealed a higher number of linguofacial trunk origins than females. It was reported that the most frequent source (51.9%) was between the inferior border of the mandible and ILA [30]. Pinar et al [25] stated that ILA emerged from the FA located superior to the angle of the mouth (22%), inferior to the angle of the mouth (8%), and over the angle of the mouth (8%), and at the angle of the mouth (60%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The blood supply to the maxillofacial region is primarily provided by multiple branches of the external carotid artery, which interweave to form a dense vascular network, ensuring adequate blood supply to this area. Specifically, the lingual artery, external maxillary artery, internal maxillary artery, and superficial temporal artery are the main blood supply branches ( Park et al, 2022 ). Among them, the external maxillary artery, as a key branch of the external carotid artery, can be palpated for a prominent arterial pulse at the junction of the anterior border of the masseter muscle and the inferior border of the mandible, providing an effective compression point for clinical management of bleeding in the mid-lower facial region.…”
Section: Induced Pluripotent Stem Cellsmentioning
confidence: 99%